Research, Development and Simulation of Quantum Cryptographic Protocols - Anghel, C. (Elektronika ir Elektrotechnika, 2013)
Cryptography is the art of hiding information. Quantum cryptography is the next level in cryptography. This paper presents the development and the software simulation of BB84 without eavesdropper, BB84 with eavesdropper, BB84 with QBTT eavesdropper detection method and BSPA quantum cryptographic communication protocol. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1700